PERAIRAN SEBAGAI LAHAN BANTU DALAM PENGEMBANGAN PERTANIAN DI LAHAN RAWA LEBAK - Djamhari, Sudaryanto (Jurnal Hidrosfir Indonesia, 2010)
Bog lebak farm, specially shallow lebak have potency to be developed to to become agriculture farm like rice field farm which is have irrigating. Farm lebak bog characteristic at the rains suffused by water and at dry season happened dryness, pond irrigate in shallow lebak bog do not go alongway so that in have paddy crop conducting to have risk lacking of water, good at a period of/ to growth or at a period of/to admission filling of fruit as a result fruit become small even do not contain, so that unattainable optimum productivity. Taken by step is to provide seed ready to plant before water pond dwindle. Seed conducted in territorial water with ploating system, by using materials, for example: bamboo, gegas leaf, and green algae from territorial water. Pursuant to result of Laboratory Majors Land, Faculty OfAgriculture, IPB, that nutricie element content can be used at phase growth of seed. Conducted of seed with system float in territorial water hence problem of is ready of seed at lebak bog farm which still suffused by water can overcome and crop will be able to be conducted at the time of water not less than 20 cm.